2008
DOI: 10.1016/j.neuropsychologia.2007.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal contributions to domain-general executive control processes during temporal context retrieval

Abstract: Neuroimaging studies have reported increased prefrontal cortex (PFC) activity during temporal context retrieval versus recognition memory. However, it remains unclear if these activations reflect PFC contributions to domain-general executive control processes or domain-specific retrieval processes. To gain a better understanding of the functional roles of these various PFC regions during temporal context retrieval we propose it is necessary to examine PFC activity across tasks from different domains, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 71 publications
5
36
0
1
Order By: Relevance
“…Alternatively, task difficulty could be related to memory strength, resulting in longer RTs for items poorly encoded. RT is often used as a marker of task difficulty and it has been employed to examine difficulty in categorization of items (Taylor & Thoroughman, 2008;Rajah, Ames, & DʼEsposito, 2007;West & Holcomb, 2002;Demb et al, 1995;Kounios & Holcomb, 1994). In the present study when activation was examined in relation to RT, differing levels of activation in DLPFC and in the anterior hippocampus were observed.…”
Section: Task Difficulty and The Default Networkmentioning
confidence: 56%
“…Alternatively, task difficulty could be related to memory strength, resulting in longer RTs for items poorly encoded. RT is often used as a marker of task difficulty and it has been employed to examine difficulty in categorization of items (Taylor & Thoroughman, 2008;Rajah, Ames, & DʼEsposito, 2007;West & Holcomb, 2002;Demb et al, 1995;Kounios & Holcomb, 1994). In the present study when activation was examined in relation to RT, differing levels of activation in DLPFC and in the anterior hippocampus were observed.…”
Section: Task Difficulty and The Default Networkmentioning
confidence: 56%
“…Although we cannot determine from our current experimental design, prior studies of the specific cognitive processes mediated by distinct nodes of activity, such as left DLPFC, have emphasized the role of left DLPFC during successful context retrieval (Thaiss and Petrides, 2003;Dobbins et al, 2004;Mitchell et al, 2004Mitchell et al, , 2006, and have suggested that this region is involved in mediating cognitive control processes during memory retrieval, such as retrieval search, response selection, and/or postretrieval monitoring (Rajah et al, 2008). Similarly, several studies have reported greater inferior parietal cortex activity during retrieval success (Wagner et al, 2005).…”
Section: Age-related Changes In Right More Than Left Mfg Volumementioning
confidence: 88%
“…The stimuli have been used in several context memory tasks in the laboratory (Rajah et al, 2008(Rajah et al, , 2010, and details about the stimuli can be found in Rajah et al (2008Rajah et al ( , 2010. The set of stimuli used for each memory task was balanced for age, gender, and neutral/pleasantness rating.…”
Section: Behavioral Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that bilateral DLPFC and frontopolar activity increased with the number of subprocesses required to make the test decision, but not with the level of supporting evidence in memory (also see Hayama, Johnson, & Rugg, 2008;Rajah, Ames, & DʼEsposito, 2008). The exact nature of the decision rules used in these tasks as well as the degree that they may have relied on recollection and familiarity is unclear.…”
Section: Introductionmentioning
confidence: 99%